Horizontal ridge reconstruction of the anterior maxilla using customized allogeneic bone blocks with a minimally invasive technique - a case series - Laurent Venet; Michel Perriat; Francesco Guido Mangano; Thomas Fortin (BMC, 2017)
Abstract Background Different surgical procedures have been proposed to achieve horizontal ridge reconstruction of the anterior maxilla; all these procedures, however, require bone replacement materials to be adapted to the bone defect at the time of implantation, resulting in complex and time-consuming procedures. The purpose of this study was to describe how to use a 3D printed hardcopy model of the maxilla to prepare customized milled bone blocks, to be adapted on the bone defect areas using a minimally invasive subperiosteal tunneling technique. Methods Cone beam computed tomography (CBCT) images of the atrophic maxilla of six patients were acquired and modified into 3D reconstruction models. Data were transferred to a 3D printer and solid models were fabricated using autoclavable nylon polyamide. Before the surgery, freeze-dried cortico-cancellous blocks were manually milled and adapted on the 3D printed hardcopy models of the maxillary bone, in order to obtain customized allogeneic bone blocks. Results In total, eleven onlay customized allogeneic bone grafts were prepared and implanted in 6 patients, using a minimally invasive subperiosteal tunneling technique. The scaffolds closely matched the shape of the defects: this reduced the operation time and contributed to good healing. The patients did not demonstrate adverse events such as inflammation, dehiscence or flap re-opening during the recovery period; however, one patient experienced scaffold resorption, which was likely caused by uncontrolled motion of the removable provisional prosthesis. Following a 6 month healing period, CBCT was used to assess graft integration, which was followed by insertion of implants into the augmented areas. Prosthetic restorations were placed 4 months later. Conclusions These observations suggest that customized bone allografts can be successfully used for horizontal ridge reconstruction of the anterior maxilla: patients demonstrated reduced morbidity and decreased total surgery time. Further studies on a larger sample of patients, with histologic evaluation and longer follow-up are needed to confirm the present observations.